Individual and community level factors associated with modern contraceptive utilization among married women in the emerging region of Ethiopia: a multilevel mixed effects analysis of the 2019 Ethiopia Mini-Demographic and health survey - Natnael Kebede; Bereket Kefale; Muluken Yigezu; Eyob Ketema Bogale; Amare Zewdie; Yitbarek Wasihun; Metadel Adane (BMC Women's Health, 2023)
Abstract Background A demonstrated technique to enhance reproductive health and economic progress is through ensuring that family planning services are accessible universally. Those studies that used Ethiopia Demographic and Health Survey (EDHS) data did not assess individual and community-level factors in contraceptive utilization. Thus, the study employs a multilevel mixed effects analysis approach, which allows for the examination of individual and community-level factors that influence contraceptive utilization. Methods This study analyzed the 2019 Ethiopia Min Demographic and Health Survey datasets. A total of 1916 married women in the 2019 surveys were included in the analysis. The data were analyzed using Stata version 17.0. The data were analyzed using Multi-level mixed-effect logistic regression to identify the individual and community-level factors associated with modern contraceptive utilization. An adjusted odds ratio with a 95% confidence interval was used to. Show the strength and direction of the association and statistical significance was declared at a P value less than 0.05. Results Factors significantly associated with modern contraceptive utilization were; Muslim and protestant followers [AOR = 0.31, 95% CI: (0.134, 0.714)] and [AOR = 0.35, 95% CI: (0.173, 0.691)] respectively, women with no education (OR = 0.46; 95% CI: 0.293, 0.710), those women who belong to the poor and middle wealth of household [AOR = 0.35, 95% CI: (0.237, 0.527)] and [AOR = 0.56, 95% CI: (0.347, 0.919)] respectively, women who had one to five and greater than or equal to six living children [AOR = 11.36, 95% CI:(2.119, 60.918)] and [AOR = 7.44, 95% CI:(1.437, 38.547)]respectively, Women in clusters poor wealth status [AOR = 0.40, 95% CI: (0.183, 0.875)] and women who belong to the Somali region [AOR = 0.20, 95% CI: (0.0.070, 0.506)]. Conclusion The study revealed that both individual and community-level factors determined modern contraceptive utilization. At the individual level, the religion of women, educational status, the wealth of the household, and the total number of living children were significantly associated with modern contraceptive utilization. At community-level factors, community wealth status and belonging to the Somali region were significantly associated with modern contraceptive utilization. The findings suggest that interventions aimed at increasing modern contraceptive utilization should target women with lower levels of education, those living in households with lower wealth, and those with larger families. Additionally, efforts should be made to improve access to modern contraceptives in communities with lower wealth status and in regions where traditional beliefs may hinder their use.